2018
DOI: 10.1002/cche.10049
|View full text |Cite
|
Sign up to set email alerts
|

Falling number of soft white wheat by near‐infrared spectroscopy: A challenge revisited

Abstract: Funding information USDA-ARS; Washington Grain CommissionBackground and objectives: Wheat Hagberg falling number (FN) is a longstanding quality test that, by means of measuring the viscosity of a heated watermeal or water-flour mixture, characterizes the activity of endogenous a-amylase, the enzyme primarily responsible for starch hydrolysis. The accuracy, time requirement, and cost of this test have come under heightened scrutiny, particularly in seasons when weather conditions have been favorable to preharve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 13 publications
1
28
3
Order By: Relevance
“…[ 10,43 ] It has been reported that precipitation reduces the grain drying rate, [ 44 ] upon water absorption by the grain endosperm. [ 40 ] In addition, it stimulates the production of the plant hormones associated with the germination (i.e., gibberellic acid), [ 45 ] which then promotes the activity of α‐amylase. [ 4 ] However, the data presented showed that the increase in enzyme activity of grain exposed to rain was not accompanied by any visible sprouting symptoms in both cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10,43 ] It has been reported that precipitation reduces the grain drying rate, [ 44 ] upon water absorption by the grain endosperm. [ 40 ] In addition, it stimulates the production of the plant hormones associated with the germination (i.e., gibberellic acid), [ 45 ] which then promotes the activity of α‐amylase. [ 4 ] However, the data presented showed that the increase in enzyme activity of grain exposed to rain was not accompanied by any visible sprouting symptoms in both cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…[48] Such conditions may favor the harvest of mature grains before the induction of -amylase by precipitation at harvest time. [45] Another possible explanation is that a temperature of 15°C lead to delay in wheat germination compared to 20°C, [49] since the germination inhibitor (e.g., abscisic acid) is maintained in the embryo. [19] The chemical components of wheat grains were influenced by cultivar and site at most grain development stages (Tables 2 and 3 and Figure 3).…”
Section: Enzyme Activity and Chemical Components During Grain Ripeninmentioning
confidence: 99%
“…Based on the PLSR models, the kernel format had better performance (𝑅 2 C = .708), which was still poor in accuracy. When the two formats were combined into a larger dataset, the model performance became worse (Delwiche et al, 2018). The only acceptable result was achieved by Sujka et al (2017) using MIRS, where the 𝑅 2 P was .95 as predicted by the PLSR model based on specific spectral ranges.…”
Section: Germination/falling Numbermentioning
confidence: 99%
“…Recent reviews and reports have also highlighted the ability of NIR spectroscopy to predict different parameters associated with starch physicochemical characteristics, most of them associated with functional properties in cereals and other starchy foods [36][37][38][39].…”
Section: Cereals and Starchy Foodsmentioning
confidence: 99%